Intersectoral knowledge spaces of emerging technologies and innovation opportunities for established industrial sectors - Sousa, C.; Fontes, M.; Barbosa, J. (Journal of the Knowledge Economy)
The paper investigates how the emergence of new sustainable technologies can induce innovation and change in the industrial sectors that contribute competences and resources to their development. For this, it develops and tests a framework to address knowledge recombination processes at the intersection of diverse sectoral knowledge bases. The paper maps the intersectoral knowledge space formed as part of the emergence of a new sustainable technology, marine renewable energy, and proposes that the position of a sector in that space – in terms of variety of connections and (un)relatedness between the connected sectors – is associated with differentiated opportunities for innovation and engagement in diversification into a new business. This research contributes to the literature on the industrial transformative effects of new technologies by uncovering some of the processes through which intersectoral knowledge relationships generate opportunities for knowledge (re)combination and innovation in firms from existing sectors. The results can inform policies that aim to combine sustainability and industrial development goals.